BULL ENGINEERING: SPERMATOGONIAL STEM CELLS TRANSPLANTATION (Veterinária Notícias, 2021)
Spermatogonial Stem Cell (SSC) transplantation is a biotechnology that consists in the transfer of testicular stem cells from a fertile donor to an infertile recipient. This technique can be applied to the production of males that generate a progeny with genotypic characteristics of the selected donor. Especially in beef and dairy cattle, SSC’s transplantation has the potential to replace artificial insemination (AI). In addition, it has other applications such as restoration of fertility in men after cancer treatment, endangered species extinction conservation and infertility treatment. Thus, the purpose of this review is discuss reproduction biotechnology that allows the propagation of the higher genetic value of males.